Effects of Lake Nam Co and Surrounding Terrain on Extreme Precipitation Over Nam Co Basin, Tibetan Plateau: A Case Study. Issue 10 (18th May 2022) - Zhao, Zhizhan; Huang, Anning; Ma, Weiqiang; Wu, Yang; Wen, Lijuan; Lazhu,; Gu, Chunlei
Abstract: Thousands of lakes and complex topography on Tibetan Plateau (TP) have important impacts on the local weather and climate, especially extreme weather events. In this study, the Weather Research and Forecasting model was adopted to quantify the impacts of Lake Nam Co (LNC) and surrounding topography on the extreme snowfall event over Nam Co basin on 24 October 2006 based on numerical experiments. The accumulated precipitation of 12 hr in this event is characterized by a maximum precipitation center with an intensity exceeding 20 mm over eastern LNC and downwind regions. Results show that the precipitation regionally averaged over eastern LNC and downstream regions can be reduced by 53%, 26%, and 68% when LNC, surrounding terrain, and both of them are absent, respectively, suggesting that LNC plays a dominant role in the formation of this event while the surrounding mountains further amplify the lake effect precipitation/snow over the downwind of LNC. Mechanism analysis indicates that the low‐level convective instability and water vapor convergence induced by LNC are essential for the formation of this extreme snowfall event, while the wind deflection and topographic lifting further strengthen the precipitation over the downwind of LNC and shift the snow belt distribution. This study is not only important to deepen the understanding of the complex interactions between the lake and orography and their combined influences on regional extreme precipitation, but also helpful for further improving the refined forecasting of the extreme precipitation induced by the lake and surrounding terrain in other regions over TP. Plain Language Summary: Lakes and complex terrain over Tibetan Plateau (TP), which is well known as "Asia's Water Tower" and "Roof of the World, " play important roles in extreme weather events. To indicate the impacts of lakes and surrounding terrain over TP on extreme precipitation/snow, the Weather Research and Forecasting model, which can well reproduce the extreme snowfall event over Nam Co basin on 24 October 2006 in terms of intensity and distribution, is used to quantify the effects of Lake Nam Co (LNC) and surrounding topography on this event by a case study. We found that LNC played a dominant role in providing water vapor and energy for the formation of the extreme snowstorm while the lifting effect of Nyainqentanglha Mountains on the westerlies from the LNC further enhanced and redistributed the lake effect precipitation/snow over the downwind of LNC. This preliminary exploration deepens our understanding of the combined effects of lake and surrounding terrain on the extreme snowfall/precipitation under a certain atmospheric circulation background to some extent. Findings of this study can provide a base to further improve the refined prediction level of extreme snowfall/precipitation over lakes and surrounding areas on TP. Key Points: The extreme snowfall over Nam Co basin on 24 October 2006 cannot be reproduced without Lake Nam Co (LNC) and surrounding topography The hydrothermal effect of LNC plays a dominant role in the formation of the extreme snowfall event The terrain lifting effect on the westerlies from LNC further amplifies the lake effect snow over the downwind of the lake